Quality of life of children with residual seizures after epileptic resection surgery - Wu, Yuxin; Zhang, Zaiyu; Liang, Ping; Zou, Bin; Wang, Difei; Zhai, Xuan (Frontiers in Neurology, 2022)
Abstract OBJECTIVE: Epilepsy dramatically affects the quality of life (QoL) of children, and resection surgery can improve QoL by reducing or completely controlling seizures. Children having postoperative seizures tend to have a poorer QoL. The aim of the present study was to investigate the QoL of children with seizures after resection surgery and the influencing factors. METHODS: We retrospectively reviewed 151 consecutive children who underwent resection surgery and divided them into seizure and seizure-free groups according to their seizure outcomes 1 year after surgery. Variables were categorized into preoperative factors, surgery-related factors, postoperative factors, and family factors. QoL and seizure outcomes more than 3 years after surgery were assessed according to the ILAE seizure outcome classification and the CHEQOL-25 scale. RESULTS: Forty-three (28.5%) of the 151 children had seizures 1 year after surgery, and two children died during the follow-up period. The mean CHEQOL-25 scale for children with seizures was 63.5 ± 18.2, and 20 (48.8%) patients had poor QoL. Surgery-related factors, such as surgical complications and surgical sequelae, were not statistically associated with QoL. Preoperative language development retardation or language dysfunction (OR = 29.3, P = 0.012) and postoperative ILAE seizure outcome classification (OR=1.9, P = 0.045) were significantly associated with QoL. SIGNIFICANCE: Children with seizures after resection surgery had relatively poor QoL. Surgery-related factors such as surgical complications and surgical sequelae cannot predict QoL. Preoperative language development retardation or language dysfunction and postoperative ILAE seizure outcome classification were independent predictors of quality of life. For children who could not achieve seizure freedom after surgery, a lower ILAE grade (ILAE 1-3) is also an acceptable outcome since it predicts a higher QoL.